The Relationship Of Characteristics Of Maternal With The Duration Of Placenta Removal In The Bio Clinic In 2022 - Yanti; Afrida Yelni; Faradita Wahyuni (International Archives of Medical Sciences and Public Health, 2022)
Hemorrhage with retained placenta accounts for a small proportion of cases of postpartum hemorrhage, but the incidence of retained placenta accounts for the maternal mortality rate due to retained placenta and the incidence is 0.8-1.2% for each birth. The cause of retained placenta between the placenta has not been separated from the uterine wall and the placenta has separated, but has not been born. Based on the above background, the formulation of the problem in this study is how the characteristics of the mother in labor and the duration of placental separation at the Biological Clinic in 2022. The research design used in this study was an analytical survey with a cross sectional approach. This is done to explore how and why the phenomenon occurs, and to study the relationship between the independent variable and the dependent variable. Population is the whole object of research or object under study. In this study, the population was all mothers who gave birth at the Biological Clinic as many as 153 people. Sampling in this study using the Slovin formula as many as 60 people. With Random Sampling Technique. The results of statistical tests with Chi-square at = 0.05 obtained P value = 0.006 (p>?), thus showing that there is a significant relationship between maternal age and the duration of placental separation. The results of statistical tests with Chi-square at = 0.05 obtained P value = 0.023 (p>?), thus showing that there is a significant relationship between maternal parity and the duration of placental separation. Conclusion In this study, it can be seen that there is a relationship between maternal characteristics and the duration of placental separation at the Biological Clinic in 2022. It is recommended as input so that future researchers can make this research a comparison with previous research and it is hoped that researchers will be able to develop this study with variables that different.